PENGECEKAN KESEHATAN GRATIS DAN PEMBERIAN INFORMASI KESEHATAN DI DESA BINAAN TATAH LAYAP KABUPATEN BANJAR - Aulia Rahim; Yugo Susanto; Erna Prihandiwati; Novia Ariani; Amaliyah Wahyuni; Noor Aisyah; Rakhmadhan Niah; Eka Kumalasari; Riza Alfian (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Lack of public knowledge, so it is necessary to provide information related to health in order to increase public awareness of health, especially for degenerative diseases or non-communicable diseases. The purpose of carrying out this community service is to increase public understanding and raise awareness of the importance of maintaining health from an early age. The implementation method used is face-to-face with pharmacists after they have checked their health and then proceed with providing health information to patients. The results of the implementation of providing health information were attended by 63 participants from the assisted village of Tatah Layap with details of 30 people checking blood sugar, 23 people checking uric acid, and 10 people checking cholesterol. The conclusion of the implementation of this activity is that the community's understanding is increasing and better after providing health information and becoming more aware of the importance of maintaining health from an early age.